Developing Management from Islamic Perspectives (MIP) as a Formal Academic Discipline (American Journal of Islam and Society, 2009)
Management from Islamic Perspectives (MIP) is an emerging field that has begun to attract scholarly attention. However, the research undertaken so far has been rather fragmented and lack a clear agenda. This paper presents a literature review of the field and the areas of current focus. Although the field has a huge growth potential, I argue that it faces several challenges and problems as it develops further. I outline these potential pitfalls, suggest how to develop MIP as a formal discipline, and explain how to integrate it within real-life business practices. The article closes with a call for research to be conducted in a more organized fashion through an international consortium of researchers as well as recommendations for future research directions.